2022
DOI: 10.1186/s13054-021-03882-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time to intubation on mortality and pulmonary sequelae in critically ill patients with COVID-19: a prospective cohort study

Abstract: Question We evaluated whether the time between first respiratory support and intubation of patients receiving invasive mechanical ventilation (IMV) due to COVID-19 was associated with mortality or pulmonary sequelae. Materials and methods Prospective cohort of critical COVID-19 patients on IMV. Patients were classified as early intubation if they were intubated within the first 48 h from the first respiratory support or delayed intubation if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 38 publications
2
46
1
1
Order By: Relevance
“…Patients with delayed onset of invasive ventilation have increased mortality and more severe pulmonary sequelae in terms of lung carbon monoxide diffusion capacity (DLCO) and radiological imaging ( 105 ). One possible explanation may be that maintaining patients with NIV when not appropriate can trigger patient self-induced lung injury (P-SILI) due to increased inspiratory efforts ( 105 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with delayed onset of invasive ventilation have increased mortality and more severe pulmonary sequelae in terms of lung carbon monoxide diffusion capacity (DLCO) and radiological imaging ( 105 ). One possible explanation may be that maintaining patients with NIV when not appropriate can trigger patient self-induced lung injury (P-SILI) due to increased inspiratory efforts ( 105 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with delayed onset of invasive ventilation have increased mortality and more severe pulmonary sequelae in terms of lung carbon monoxide diffusion capacity (DLCO) and radiological imaging ( 105 ). One possible explanation may be that maintaining patients with NIV when not appropriate can trigger patient self-induced lung injury (P-SILI) due to increased inspiratory efforts ( 105 ). Therefore, in addition to NIV comfort, it is of pivotal importance to monitor predictors of failure of NIV, i.e., no change or worsen in pH, blood gases, respiratory rate, and agitation ( 19 ), to early intervene with intubation and not worsen patients' prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also found that the reduction in dorsal LUS score > 1 in the first APP session predicted the treatment success. Importantly, this finding can help early identify those patients with high risk of APP failure, who might benefit from more intensive monitoring and early treatment escalation and not delay intubation [ 21 ]. Thus, LUS assessment may be a very useful tool in the day-to-day clinical decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive MV via a tracheal tube appears to be the most common approach after failed NIV but is associated with higher all-cause mortality in COVID-19 patients [ 10 , 11 , 12 ]. Contrasting results have been published regarding early intubation in terms of survival benefits [ 13 , 14 , 15 , 16 , 17 ]. Tracheostomy is considered an effective alternative to invasive MV via tracheal tube since it helps to reduce dead-space ventilation and decreases airway resistance and the risk of aspiration, as well as the need for sedation, facilitating weaning from a ventilator [ 18 ].…”
Section: Introductionmentioning
confidence: 99%